Lilly$1 (Bs big day s - Henkes, Kevin (New York : Greenwillow Books, 2005)
When her teacher announces that he is getting married, Lilly the mouse sets her heart on being the flower girl at his wedding.
Keywords: Mice -- Fiction; Weddings -- Fiction; Teachers -- Fiction